1986
DOI: 10.1111/j.1939-0025.1986.tb02720.x
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate risk model for childhood behavior problems.

Abstract: In a study of 306 children whose parents have a mental illness, the relationship between coping skills and environmental assets and deficits determined the degree of behavior problems among these high-risk children. Two environmental stressors (proportion of mentally ill family members and mother-child discord), two coping skills (activity competence and school competence), and an interaction (between proportion of mentally ill family members and activity competence) were found to explain 40% of the variance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Studies indicate that better school achievement is associated with fewer behaviour problems (e.g., Stiffman et al, 1986;Werner & Smith, 1982), but studies do not always distinguish between aggressive behaviour and impulsive, distractible, hyperactive behaviour. The present findings indicate that this is an important distinction because only hyperactivity/inattention was associated with academic performance.…”
Section: Pathways To Academic Performancementioning
confidence: 97%
See 1 more Smart Citation
“…Studies indicate that better school achievement is associated with fewer behaviour problems (e.g., Stiffman et al, 1986;Werner & Smith, 1982), but studies do not always distinguish between aggressive behaviour and impulsive, distractible, hyperactive behaviour. The present findings indicate that this is an important distinction because only hyperactivity/inattention was associated with academic performance.…”
Section: Pathways To Academic Performancementioning
confidence: 97%
“…We hypothesised that better emotional and behavioural functioning would be associated with better academic performance (Jimerson, Egeland, & Teo, 1999;Rae-Grant et al, 1989;Stiffman, Jung, & Feldman, 1986), and with higher levels of prosocial behaviour RaeGrant et al).…”
Section: Specific Hypotheses Tested (Pathways In the Conceptual Model)mentioning
confidence: 97%
“…Results of Rutter's studies identified the following variables as protective components which figure significantly in the stress of parental separation on children: a supportive, stable and cohesive family climate; a good relationship with at least one parent; and supportive school settings themselves. Stiffman et al (1985) emphasized that the social system in which an individual lives has features that may serve as stressors or protectors to the child. Environmental protectors to the child whose parent has a mental illness include supportive peer groups, accessible social services, parental employment and marital happiness.…”
Section: In the Unitedmentioning
confidence: 99%
“…Good personal relationships and social supports may mitigate the effects of stressful life events (Lamb, 1977;Anthony, 1980;Rutter, 1981;Wallerstein-Kelly, 1980;Hetherington et al, 1980;Stiffman, 1985;Thoits, 1986 Thoits (1986) suggests that social support may be conceptualized as a "coping assistance" and thus usefully integrate coping processes and support processes within a broader theory of "stress-buffering".…”
Section: )mentioning
confidence: 99%
“…Further, Hispanic youth may not possess an inherent awareness of stressors in their lives, let alone the ability to remove or deal with them (Snyder, Dishion, and Patterson, 1986;Stiffman, Jung, and Feldman, 1986). Less than ideal living conditions, language barriers, and early socialization processes may leave Hispanic adolescents ill-prepared to cope with external and internal demands.…”
Section: Copingmentioning
confidence: 99%